Obravnava bolnikov s srčnim popuščanjem v splošni in univerzitetni bolnišnici v letu 1997 - Keber, Irena (Zdravniški vestnik, 2003)
Background. Chronic heart failure is a serious condition with high morbidity and mortality. Prognosis can be improved with early diagnosis and adequate nonpharmacologic and pharmacologic treatment. Aims of the study. Aim of the study was a comparison of diagnostic and therapeutic management of patients who were hospitalized in the University or Community hospital Methods. The hospital records of patients, hospitalized for heart failure, from University hospital (UH, Internal clinic, Department of angiology, Department of hypertension) and Community hospital (CH, Department of Internal medicine) were reviewed retrospectively. We included all consecutive patients in the period from January 1, 1997 to June 30, 1997 (CH) and December 31, 1997 (UH) who were discharged or died with diagnosis of a heart failure. Results. Six hundred and twenty five patients (307 from CH and 318 from UH), aged 76 11 years, were included in the survey. In 308 (49%) patients heart failure was diagnosed prior to index hospitalization. Rehospitalization rate was 42%. Etiology of heart failure was ischemic heart disease (36%), arterial hypertension (37%), dilated cardiomyopathy (16%) and valvular heart disease (15%). The hospital stay was 14 10 days in UH and 10 6 days in CH (p < 0.001). Overall in-hospital mortality reached 16% (98 patients) and was 8% in UH and 24% in CH (< 0.001). Echocardiography was performed in UH in 45% and inCH in 13 % of all patients and in 50% vs. 22% of patients, hospitalized for the first time. At the discharge the following drugs were prescribed (UH vs. CH): diuretics (82% vs. 73%), ACE inhibitors (61% vs. 33%), digoxin (54% vs. 71 %) beta-adrenergic blockers (3% vs. 0%) and antiarrhytmics (7% vs. 32%). (Abstract truncated at 2000 characters).
Keywords: Bolnišnice splošne; Bolnišnice univerzitetne; cardiovascular disease; Diagnosis; diagnostika; Drug Therapy; heart; Heart Failure, Congestive; Hospitals, General; Hospitals, University; kardiovaskularne bolezni; Retrospective Studies; Retrospektivne študije; srce; Srce, odpoved kongestivna; srčno popuščanje; Therapy; zdravljenje